2020
DOI: 10.1002/2211-5463.12962
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐electron microscopy visualization of a large insertion in the 5S ribosomal RNA of the extremely halophilic archaeon Halococcus morrhuae

Abstract: The ribosome is an ancient and universal ribonucleoprotein molecular machine, with fingerprints of ancient and recent insertions seen in its structure. The extremely halophilic archaeon Halococcus morrhuae (ATCC ® 17082) possesses an unusual insertion in the 5S rRNA, almost doubling its length. Cryo‐EM reveals a four‐way junction at the insertion site, accommodating the insert without disrupting the canonical 5S structure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…are characterized by the presence of so-called expansion segments (ES), which are additional RNA elements of various sizes incorporated into the universal prokaryotic rRNA core (Gerbi, 1996;Bowman et al, 2020; Figure 1). These ES increase the size and complexity of the respective rRNAs; however, recent analyses have provided evidence for the presence of such ES in both bacteria and archaea (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021). Although most of these sequence additions are limited in size and number (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021), larger ES, similar in size to those commonly observed in eukaryotes, have been recently described in the Asgard archaeal phylum (Penev et al, 2020), which is proposed to be the cradle of the eukaryotic lineage (Spang et al, 2015;Zaremba-Niedzwiedzka et al, 2017;.…”
Section: Ribosomal Subunit Composition: Archaeal Specificity and Common Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…are characterized by the presence of so-called expansion segments (ES), which are additional RNA elements of various sizes incorporated into the universal prokaryotic rRNA core (Gerbi, 1996;Bowman et al, 2020; Figure 1). These ES increase the size and complexity of the respective rRNAs; however, recent analyses have provided evidence for the presence of such ES in both bacteria and archaea (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021). Although most of these sequence additions are limited in size and number (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021), larger ES, similar in size to those commonly observed in eukaryotes, have been recently described in the Asgard archaeal phylum (Penev et al, 2020), which is proposed to be the cradle of the eukaryotic lineage (Spang et al, 2015;Zaremba-Niedzwiedzka et al, 2017;.…”
Section: Ribosomal Subunit Composition: Archaeal Specificity and Common Featuresmentioning
confidence: 99%
“…These ES increase the size and complexity of the respective rRNAs; however, recent analyses have provided evidence for the presence of such ES in both bacteria and archaea (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021). Although most of these sequence additions are limited in size and number (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021), larger ES, similar in size to those commonly observed in eukaryotes, have been recently described in the Asgard archaeal phylum (Penev et al, 2020), which is proposed to be the cradle of the eukaryotic lineage (Spang et al, 2015;Zaremba-Niedzwiedzka et al, 2017;. However, a common evolutionary relationshipbased on sequence and/or structure homology-of the larger archaeal and eukaryotic ES could not be established (Penev et al, 2020).…”
Section: Ribosomal Subunit Composition: Archaeal Specificity and Common Featuresmentioning
confidence: 99%
“…Furthermore, in studies on halophilic archaea, ribosome stability is known to be severely affected in low-salt concentration buffers ( 112 , 113 ). However, despite the salt requirement for its stability, the overall basic structure of the ribosome in extreme halophilic archaea, such as H. morrhuae ( 113 ) or H. marismortui ( 114 , 115 ), is similar to that found in bacteria. The amino acid residues are reported to undergo significant intermolecular segregation along the ribosomal proteins based on their charges.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in studies on halophilic archaea, the stability of ribosomes is known to be severely affected at low-salt concentration buffers (115,116). However, despite the salt requirement for its stability, the overall basic structure of the ribosome from extreme halophilic archaea such as H. morrhuae (116) or H. marismortui (117,118), is similar to those found in bacteria. The amino acid residues are reported to undergo significant intermolecular segregation along the ribosomal proteins, based on their charges.…”
Section: Implications Of Net Charges On Translational Rate(s) and Ribosome Stabilitymentioning
confidence: 96%